Educação continuada do catalogador na modalidade a distância: uma proposta alternativa - Pereira, Ana Maria; Santos, Plácida Leopoldina Ventura Amorim da Costa [UNESP] (Pontifícia Universidade Católica de Campinas, 2004)
This paper presents a proposal for the teaching of cataloguing, emphasizing the problem-solving methodology. The proposal was designed for the distance-based continuing education of the professional cataloguer. It takes into account the challenges inherent to the development of interactive and inter-disciplinary tasks, as well as the development of directed self-education and critical consciousness of that professional, inasmuch as he becomes an active subject, manager of his/her own education.

Apresenta uma proposta para o ensino de catalogação, com ênfase na Metodologia da Problematização. A proposta está voltada para a educação continuada a distância do profissional catalogador, e leva em conta os desafios implicados no desenvolvimento da interatividade, da interdisciplinaridade, da auto-educação e da consciência crítica desse profissional, uma vez que ele se torna sujeito ativo e gerenciador de sua própria educação.
Cataloguer's distance-based continuing education: an alternative proposal
Keywords: Educação continuada; Educação a distância; Catalogação; Metodologia da problematização; Continuing education; Distance-based education; Cataloguing; Problem-solving methodology